An Investigation into the Correlation between IETLS Test Preparation Course and IELTS Writing Score and Students’ Reflective Journals - AL AWADI, FATEMA EBRAHIM MOHAMED SAEED (2018)
English language usage is becoming a priority in higher education studies in the UAE. Testing English skills for EFL learners through the International English Language Testing System (IELTS) has been given greater attention as a requirement for students’ admission and graduation. Moreover, the need to develop language skills for the test is important through preparation, since it adds to the language knowledge of EFL learners and train them to deal with skill related tasks. The preparation courses can change students’ attitudes toward language learning for academic purposes, which can also affect their learning of other courses at universities. That can impact the students’ written texts and assignments that require writing reports and understanding specific genres. This study aims to investigate the correlation of IELTS test scores and preparation courses and students’ writing of reflective journals in education. A discourse analysis of different levels’ reflections gained from three participants were selected from one of the federal colleges in the UAE was carried out. The data were gathered from students’ scores in IELTS reports, samples of preparation course materials and interviews with participants. The results of the research found that IELTS test scores cannot be guaranteed to measure the students’ true ability. Preparation courses seem to have an impact on the language learning ability, writing performance and understanding. Two participants benefited from taking the IELTS preparation courses, while the third had good language skills developed due to other factors such as; college studies, strong language foundations in schools and a desire to learn English. The study also revealed that there are other challenges affecting IELTS test reliability and the correlation with reflections such as the test assessors, different marking schemes and different requirements of IELTS test and academic assessments.